BECOS DA MEMÓRIA: A (DES) CONSTRUÇÃO DE UM (NÃO) LUGAR PARA VOZES SILENCIADAS - Dias, Mileide Santos (2020)
This master‟s dissertation predicts an analysis of the work Becos da Memória (2013) by Conceição Evaristo. A discussion was developed on how the territorial denials imposed on black population transcend geographical aspects, reach Afro-Brazilian sub